ePortfolio Performance Support Systems Constructing, Presenting, and Assessing Portfolios - Wills, Katherine V.; Rice, Rich (Open textbook library., 2013)
ePortfolio Performance Support Systems: Constructing, Presenting, and Assessing Portfolios addresses theories and practices advanced by some of the most innovative and active proponents of ePortfolios. Editors Katherine V. Wills and Rich Rice interweave twelve essays that address the ways in which ePortfolios can facilitate sustainable and measureable writing-related student development, assessment and accountability, learning and knowledge transfer, and principles related to universal design for learning, just-in-time support, interaction design, and usability testing.